TANGGUNG JAWAB PELAKU USAHA SEBAGAI PENGANGKUT BARANG YANG OVER DIMENSION & OVERLOAD (ODOL) BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Nicholas Rachmanata; Amad Sudiro (Jurnal Hukum Adigama, 2022)
Over Dimension and Over Load (ODOL) carried out by business actors always steals the government's attention considering that this is not only dangerous for road users, but also causes financial losses to the state. The aspect of state losses as a result of ODOL is damage to roads, forcing more budget to be spent to repair these damaged roads. Business actors in carrying out business activities bear the burden of responsibility to be able to provide benefits in all aspects and cannot be separated from the safety aspect for other road users. The phenomenon of ODOL that is attached to society encourages the government to enforce the law on aspects of the responsibilities of business actors so that through this research a descriptive analysis of UULLAJ is carried out using normative juridical research methods supported by data from interviews with relevant stakeholders. ODOL carried out by business actors is an unlawful act, one of which is caused by economic factors (supply and profit) in the goods distribution process carried out between consumers and business actors, forcing business actors to continue to carry out ODOL even though they already know the legal consequences. The regulation of ODOL in society is still not burdensome for the perpetrators, such as the amount of fines imposed is still relatively small and far from providing a deterrent effect, thus creating a legal culture of indifference in society. The state needs to carry out more supervision and law enforcement against business actors who practice ODOL.